Role of patient characteristics in adherence to first-line treatment guidelines in breast, lung and prostate cancer: insights from the Nordic healthcare system - Sandström, Niclas (BMJ Group, 2025)
Objectives This study investigates the influence of socioeconomic status, health literacy, and numeracy on treatment decisions and the occurrence of adverse events in patients with breast, lung, and prostate cancer within a Nordic healthcare setting.
Design A follow-up to a cross-sectional, mixed-methods, single-centre study.
Setting A Nordic, tertiary cancer clinic.
Participants A total of 244 participants with breast, lung and prostate cancer were initially identified, of which 138 first-line treatment participants were eligible for this study. First-line treatment participants (n=138) surpassed the expected cases (n=108).
Interventions Not applicable as this was an observational study.
Primary and secondary outcome measures The study’s primary endpoint was the rate of guideline adherence. The secondary endpoint involved assessing treatment toxicity in the form of adverse events.
Results Guideline-adherent treatment was observed in 114 (82.6%) cases. First-line treatment selection appeared uninfluenced by participants’ education, occupation, income or self-reported health literacy. A minority (3.6%) experienced difficulties following treatment instructions, primarily with oral cancer medications.
Conclusions The findings indicated lesser cancer health disparities regarding guideline adherence and treatment toxicity within the Nordic healthcare framework. A causal connection may not be established; however, the findings contribute to discourse on equitable cancer health provision.